2016
DOI: 10.1039/c6fo00929h
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin favorably modulates gut microbiota in mice fed a high-fat diet

Abstract: We investigated the anti-obesity effects of the potential prebiotic, laminarin, on mice fed a high-fat diet. A metagenomics approach was applied to characterize the ecological and functional differences of gut microbiota among mice fed a normal diet (CTL), a high-fat diet (HFD), and a laminarin-supplemented high-fat diet (HFL). The HFL mice showed a slower weight gain than the HFD mice during the laminarin-feeding period, but the rate of weight gain increased after the termination of laminarin supplementation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 58 publications
13
51
0
Order By: Relevance
“…Moreover, HFD administration could lead to typical obesity‐driven dysbiosis in the gut microbiota by increasing Firmicutes relative abundance and decreasing Bacteroidetes relative abundance . On the other hand, supplementation with polyphenols, polysaccharides, and other functional ingredients could reduce the ratio of Firmicutes to Bacteroidetes, which contributed to the prevention of body weight gain induced by HFD . In the present study, FBT could significantly reduce the ratio of Firmicutes to Bacteroidetes, suggesting that the modulation of gut microbiota to decrease the energy harvest might contribute to attenuating the obesity induced by HFD.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, HFD administration could lead to typical obesity‐driven dysbiosis in the gut microbiota by increasing Firmicutes relative abundance and decreasing Bacteroidetes relative abundance . On the other hand, supplementation with polyphenols, polysaccharides, and other functional ingredients could reduce the ratio of Firmicutes to Bacteroidetes, which contributed to the prevention of body weight gain induced by HFD . In the present study, FBT could significantly reduce the ratio of Firmicutes to Bacteroidetes, suggesting that the modulation of gut microbiota to decrease the energy harvest might contribute to attenuating the obesity induced by HFD.…”
Section: Discussionmentioning
confidence: 53%
“…reported that HFD can induce an increased abundance of Firmicutes and a decreased abundance of Bacteroidetes in the intestine. [ 62 ] Another study reported that HFD increased the abundance of LPS‐producing Proteobacteria and decreased the abundance of Tenericutes that are positively related to the content of short‐chain fatty acids (SCFAs). [ 63 ] Interestingly, the supplementation of LCP or Vc can effectively reduce the abundances of Firmicutes and Proteobacteria and increase the abundances of Bacteroidetes and Tenericutes in the gut of the HFD‐fed rats, which may result in an increase in the content of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that variations in the chemical structure of a prebiotic can impact its selective fermentation by bacteria [41]. For this reason, there were published large works regarding the investigation of the potential prebiotic effect of single polysaccharides, often contained in seaweeds, but employing pure standards [42][43][44]. However, it should be considered that seaweeds contain other components than also can affect GM.…”
Section: Polysaccharides From Marine Seaweedsmentioning
confidence: 99%